Identity and Narrative:A Special Female Case of Chinese Ancient Autobiography (Global Journal of Human-Social Science, 2016)
Li Qingzhao (李清照,1084-1155) is one of the most excellent and most famous female scholars in Chinese literature history, whose Epilog to Records on Metal and Stone1 (Jin Shi Lu Houxu, 金 石 录 后 序 ), as a rare female autobiography in Chinese ancient literature, has made many unique creative contributions to the development of Chinese biographic literature. As a female autobiography, Epilog to Records on Metal and Stone has covered three identities of Li Qingzhao -a daughter of a noble family, a wife of a civil official and a female scholar -and the self-recognition of the three identities constitutes the triple female perspective of her autobiography. As a lament work, Epilog to Record on Metal and Stone has integrated three dimensional narration spaces -autobiographic facts, lament for her deceased husband; biographical facts, lament for her collected objects; and historical facts, lament for the perished country. The richness, appropriateness and exquisiteness of the discourse structure for three dimensional lament under a triple female perspective have made Epilog to Records on Metal and Stone a milestone in Chinese biographical history.
Keywords: li qingzhao; epilog to records on metal and stone; autobiography; female perspective; lament